Single versus Dual-Chamber Pacing in a Sub-Saharan African Heart Center: Characteristics and Prognosis - Adoubi, Anicet Kassi; Diby, Florent; Ouattara, Pinnin; Gnaba, Ambroise; Kendja, Flavien (Cardiology and Cardiovascular Medicine, 2021)
Context: The pacemaker since the 2000s has seen technical improvements. In Sub-Saharan Africa, we often implant single-ventricular chamber pacemakers because of patients' limited financial resources. Objective: This work sought to compare our patients' characteristics and prognosis with single-chamber ventricular pacing with those with dual-chamber pacing. Methods: We conducted a retrospective study of patients implanted with pacemakers between 2006 and 2016 at Abidjan Heart Center in Ivory Coast. We compared demographic, clinical, and follow-up data of patients with single versus dual-chamber pacemakers. The endpoint was all-causes of death. Results: Of the 283 patients (67.3 ± 12.6 years; 49.1% of males) selected for the study, 189 (66,8%) had a single chamber pacemaker. Patients with this type of pacemaker were older, with more often syncopes and atrial fibrillation before implantation. Sex and underlying disease were comparable in the two groups. During follow-up, early and late complications were not statistically different. At the end of the follow-up period (median:3.67 years, IQ [2.07; 6.10], 73 patients (25.8%) were dead. In univariate Cox model analysis, a single-chamber pacemaker was associated with risk of death (RR =1.974; 95% CI [1.132,3.44], p = 0.017), as well as age, heart failure, atrial fibrillation and, left ventricular ejection fraction <0.40. In multivariate analysis, only age was a factor of poor prognosis. Conclusion: Our patients with single-chamber pacing had a more severe prognosis than patients with dual-chamber pacing. But this higher mortality was linked to older age and a more significant presence of atrial fibrillation in this group.